On Methods and Mess - Raj, Yogesh (Journal of Technology Research and Review, 2014)
Methodology after post-modernism must meet three challenges: (a) complexity / heterogeneity in the natural and social world; (b) bewildering mix of the true, false and fictive in the narratives; and (c) incompatible ideology and ethics in researchers. I argue that plurality in laws-generating models and methods takes care of natural and social complexity. Criticism of testimony enhances our capacity to discriminate truth from falsehood and from fiction. Ethnography of the self is a way to unburden ideologies from researcher’s practice. DOI: http://dx.doi.org/10.3126/jtrr.v1i1.10010 Journal of Technology Research and Review Volume 1, Number 1, 2014, pp 1-10